1999
DOI: 10.1161/01.hyp.34.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Function in Hypertension

Abstract: Much attention has been focused on the role of nitric oxide in hypertension and cardiovascular disease. More recently, the role of superoxide anion and its interaction with nitric oxide has been investigated in this context. This review will concentrate on the role of superoxide in human and experimental hypertension, paying particular attention to the potential sources of superoxide within the vasculature and discussing some of the molecular mechanisms surrounding its production and dismutation. We discuss wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
182
2
11

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 315 publications
(207 citation statements)
references
References 82 publications
12
182
2
11
Order By: Relevance
“…The increased OX in hypertensives has been attributed to the overactivity of mechanisms that increase ROS production which is mainly mediated by superoxide and hydroxyl radicals. 4,5 An alternative explanation for the high OX status observed in hypertensives, which does not exclude the former, is the impact of primary impairment of antioxidant enzymatic activity. Antioxidant enzymes constitute and represent an important part of the total antioxidant activity of aerobic cells and coordination of their functions results in the maintenance of ROS below critical levels compatible with cell viability and performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased OX in hypertensives has been attributed to the overactivity of mechanisms that increase ROS production which is mainly mediated by superoxide and hydroxyl radicals. 4,5 An alternative explanation for the high OX status observed in hypertensives, which does not exclude the former, is the impact of primary impairment of antioxidant enzymatic activity. Antioxidant enzymes constitute and represent an important part of the total antioxidant activity of aerobic cells and coordination of their functions results in the maintenance of ROS below critical levels compatible with cell viability and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is considered a state of oxidative stress (OX) that can contribute to the development of artherosclerosis 2 and other hypertension-induced organ damage. 3 Assessment of antioxidant activities and lipid peroxidation byproducts in hypertensives indicates an excessive amount of ROS and a reduction of antioxidant mechanism activity in blood, as well as in several other cellular systems, 4 including not only vascular wall cells, 5 but also those cells found in circulating blood. 6,7 Increased OX of hypertensive subjects improved with the antihypertensive treatment, and extending treatment over time increased the beneficial impact of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…13,22 In an animal model of hypertension, Tummala et al 11 reported that Ang II stimulates VCAM-1 expression via the activation of oxidative signaling pathways involving the redox-sensitive transcription factor nuclear factor-B (NF-B) and the upregulation of genes downstream from NF-B, including VCAM-1. Other groups have shown that Ang II stimulates superoxide production via a membrane-bound NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…24 -26 A major mechanism responsible for such an impairment is superoxide generated in the presence of the disease, which inactivates NO rapidly. 13,22 In various atherogenic models, the accumulation of T lymphocytes and monocytes at sites of vascular inflammation was shown to be VCAM-1 dependent. [2][3][4][5]27 Inflammatory mediators, including NF-B, are activated in part through the stimulation of superoxide production, resulting in attraction of macrophages, stimulation of foam cell formation, inflammation, and atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation